If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -4y = 2y + 4 Reorder the terms: 12 + -4y = 4 + 2y Solving 12 + -4y = 4 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 12 + -4y + -2y = 4 + 2y + -2y Combine like terms: -4y + -2y = -6y 12 + -6y = 4 + 2y + -2y Combine like terms: 2y + -2y = 0 12 + -6y = 4 + 0 12 + -6y = 4 Add '-12' to each side of the equation. 12 + -12 + -6y = 4 + -12 Combine like terms: 12 + -12 = 0 0 + -6y = 4 + -12 -6y = 4 + -12 Combine like terms: 4 + -12 = -8 -6y = -8 Divide each side by '-6'. y = 1.333333333 Simplifying y = 1.333333333
| x^2=-5*x+1-2 | | 3v=49-4v | | x^2=-5*x+1 | | 9*8*3.14=36*h*3.14 | | 36y^3-7=y-252y^2 | | pq-3p+2q= | | 9a+5b-7b+6a= | | 11m^2=31m+6 | | -12x+20=28 | | y+y^4= | | -10a-7=12 | | x^2=5*x+1 | | -2d^2+100=50 | | 7n^2+57n+8=0 | | 27+5p=72 | | 10t^21-29t=-10 | | 2r+6=2 | | [3x+4]=8 | | 4x-5y-2y=x | | 2a+3b=156 | | 3k+2=19.4 | | z+13z=8 | | 12x^2-42x+6=0 | | x=5-(1/0) | | 6(2-x)=-5(2x+4) | | h=62t-5t^2 | | x=(5/2) | | 15.9=19.9-2w | | 11+2y=-5 | | 1/x=5/2 | | -50x^3+20x^2+10x+25=0 | | r+-5=6 |